2013
DOI: 10.1007/s12029-013-9496-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy in Gastroenterology

Abstract: This article is a review the clinical effectiveness of PDT in the treatment of Barrett's esophagus and the following cancers: esophageal, gastric, biliary tract, pancreatic, and colon. This review highlights the clinical responses to PDT and discusses the possibility of enhancing the efficacy of treatment by combination with targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 99 publications
0
33
0
2
Order By: Relevance
“…PS-based fluorescence imaging has shown promising results in the detection of ovarian cancer [116, 117], pancreatic cancer [118, 119] and lung cancer [120, 121]. …”
Section: Other Photosensitizersmentioning
confidence: 99%
“…PS-based fluorescence imaging has shown promising results in the detection of ovarian cancer [116, 117], pancreatic cancer [118, 119] and lung cancer [120, 121]. …”
Section: Other Photosensitizersmentioning
confidence: 99%
“…In literature, there are some preclinical studies about the maintained organs' tumor. PDT with Pcs and PS of pancreatic cancer and colon tumor studies show that the results are encouraging toward future clinical applications of PDT for pancreatic cancer and colon tumor in literature (26)(27)(28)(29)(30)(31). Tzerkovsky et al (32) firstly reported on feasibility of efficient use of PDT with a PS of chlorin series and AAT with bevacizumab for the treatment of brain tumors in experimental models.…”
Section: Radiolabeling Resultsmentioning
confidence: 97%
“…PDT uses a systemically administered photosensitizing drug, typically prophimer sodium (Ps) 4-aminolevulinic acid (ALA), or m-tetrahydroxyphenyl chlorine, which accumulates in tumor tissue and is then activated by endoscopically delivered laser light using an appropriate wavelength (59). Ps is the most commonly used sensitizer, and is typically given intravenously 2 days prior to the endoscopic procedure to allow time for adequate absorption into the tissue.…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%